Komposisi Juvenil Spat Geloina erosa di Kawasan Mangrove Sungai Reuleung Leupung Kabupaten Aceh Besar - Muhammad Ali; Asiah ,; Mimie Saputri (Universitas Islam Negeri Ar-Raniry, 2015)
This study aims to (1) know the composition of juvenile spat of Geloina erosa, and (2) find out the ratio of juveli Spat on the estuary area of the river, the flow and the headwaters of estuary area of the river in mangrove ecosystem Reuleung River Leupung, Aceh Besar district. The study was conducted in May and June 2015 in mangrove area Reuleung River Leupung Aceh Besar district. The research location was divided into three stations, namely station 1 at estuary area, station 2 at river flow and station 3 at headwaters of estuary of Reuleung River Leupung, Aceh Besar district. The samples were taken three times at three stations. In every stations and observations, 5 plot with size 1mx1m were taken. Juvenile spat composition was analyzed by using percentage, while the ratio of juvenile Spat was analyzed by using Chi-square. The results showed that the composition of the juveniles in the estuary area was 26.09% and in the flow area was 50.00%, while at the headwaters of estuary of the river was 0%. The composition of Spat at estuary location was 1 73.01%, at two regional river flow was 50% and at 3 locations of headwaters of estuary was 0%. The ratio between juvenile Spat at the estuary area was 1:3, while at the river flow was 1:1, and at the headwaters of estuary was 0:0. The conclusions were (1) The composition of the juvenile and spat were varied, and (2) the ratio of juvenile Spat in the Reuleung River Leupung Aceh Besar district was balanced and unbalanced.